2005
DOI: 10.1074/jbc.m502449200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-Kinase Is Required for Rhinovirus-induced Airway Epithelial Cell Interleukin-8 Expression

Abstract: Rhinovirus (RV) is a common cause of asthma exacerbations. The signaling mechanisms regulating RV-induced airway epithelial cell responses have not been well studied. We examined the role of phosphatidylinositol (PI) 3-kinase in RV-induced interleukin (IL)-8 expression. Infection of 16HBE14o؊ human bronchial epithelial cells with RV39 induced rapid activation of PI 3-kinase and phosphorylation of Akt, a downstream effector of PI 3-kinase. RV39 also colocalized with cit-Akt-PH, a citrogen-tagged fluorescent fus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
115
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(131 citation statements)
references
References 57 publications
14
115
1
1
Order By: Relevance
“…Previous studies have shown that RV-39 (a major group virus)-induced IL-8 expression in epithelial cells occurred by ICAM binding and activation of PI3K (17,22). In our studies, we also found that inhibition of PI3K down-regulated both IL-8 and IL-6 mRNA induced by RV1b.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Previous studies have shown that RV-39 (a major group virus)-induced IL-8 expression in epithelial cells occurred by ICAM binding and activation of PI3K (17,22). In our studies, we also found that inhibition of PI3K down-regulated both IL-8 and IL-6 mRNA induced by RV1b.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies have shown that IL-8 gene expression in BECs infected with RV-39 is independent of viral replication, being triggered by viral endocytosis and activation of PI3K (17). Pretreatment of bronchial fibroblasts with the PI3k inhibitor LY294002 for 1 h before infection inhibited expression of IL-8 or IL-6 induced by either RV1b or UV-irradiated RV1b (Table I).…”
Section: Figurementioning
confidence: 94%
“…Despite this potential, our understanding of the signaling pathways regulating HRV-16-induced chemokine production remains limited. Recent studies, by us and others, have implicated the spleen tyrosine kinase, Syk, as well as PI3K and MAPK pathways in early, replication-independent viral signaling leading to production of CXCL8 (19,25,35). In contrast, few studies have focused on signaling involved in HRV-16-induced production of chemokines, such as CXCL10, that absolutely require rhinovirus replication for induction.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were cultured for 5 days in DMEM ϩ 10% FBS before further experimental manipulation to allow the cells to form a model type I cell monolayer (28). Normal immortalized 16HBE14o-human bronchiolar epithelial cells (HBE cells) were acquired from M. Hershenson Laboratory (University of Michigan) (8,41). HBE cells were maintained on tissue culture plastic in DMEM ϩ 10% FBS and used at passages 10 -20.…”
Section: Methodsmentioning
confidence: 99%